Railway Network of Romania’s Central Development Region: Current Situation and Evaluation of Development Plans Based on Graph Theory Model - Máthé, Csongor; Tamási, Erika; Schubert, Géza (Promet - Traffic&Transportation, 2013)
The present study focuses on the Central Development Region in Romania and attempts to highlight the deficiencies of the regional railway network, as well as to scientifically analyse the impact of new lines designed in the region. The current regional rail network is greatly determined by the historical development process of the railway, and therefore, in the first section, the most notable causes, milestones, and historical factors have been summarized. The goal of this paper has been to evaluate the current situation of the Central Region’s rail network and investigate the potential processes entailed by the line designed between Tîrgu Mureş and Sighişoara. For this, at first, some quantitative and qualitative analyses as well, including traffic and travel speed measurements have been carried out. Finally, using the analysis capabilities offered by the application of graph theory, we had the opportunity to perform a simulation with the planned rail line. Our conclusion is that the improvement of the Tîrgu Mureş rail accessibility toward Braşov could be considered as a real option, especially, as in the near feature, the motorway connection between these two important Transylvanian cities will be built, which will represent a huge challenge for the rail transport on this axis.